2022
DOI: 10.1111/1348-0421.12956
|View full text |Cite
|
Sign up to set email alerts
|

Sendai virus C protein affects macrophage function, which plays a critical role in modulating disease severity during Sendai virus infection in mice

Abstract: Sendai virus (SeV) accessory protein C limits the generation of double-stranded RNAs, defective interfering RNAs, or both, during viral transcription and replication, thereby limiting interferon-β production. Our recent in vitro analyses on murine macrophage cell lines demonstrated that this protein also contributes to restricting macrophage function, including the production of nitric oxide (NO) and inflammatory cytokines in addition to interferon-β, in infected macrophages. This study showed that depletion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…This study demonstrated that clodronate-loaded liposomes depleted airway macrophages, which caused severe viral pneumonia to develop in SeV-infected mice with the recombinant C gene deletion, but did not affect the extremity of the disease in mice with wild-type SeV. 113 The role of alveolar macrophages in the pathophysiology of MERS was investigated by researchers adopting a mouse model of MERS coronavirus infection. Human dipeptidyl peptidase 4 knockin mice had drastically increased morbidity and mortality when alveolar macrophages were depleted; however, mice with alveolar macrophages were protected from MERS-CoV-induced pneumonia and serious illness.…”
Section: Resultsmentioning
confidence: 92%
“…This study demonstrated that clodronate-loaded liposomes depleted airway macrophages, which caused severe viral pneumonia to develop in SeV-infected mice with the recombinant C gene deletion, but did not affect the extremity of the disease in mice with wild-type SeV. 113 The role of alveolar macrophages in the pathophysiology of MERS was investigated by researchers adopting a mouse model of MERS coronavirus infection. Human dipeptidyl peptidase 4 knockin mice had drastically increased morbidity and mortality when alveolar macrophages were depleted; however, mice with alveolar macrophages were protected from MERS-CoV-induced pneumonia and serious illness.…”
Section: Resultsmentioning
confidence: 92%
“…Further, we demonstrated that host factors involved in the early clearance of SeVΔC in mice are not limited to IFN-β, but might also include macrophage-specific factors. Indeed, in vivo depletion of airway macrophages during SeV ΔC infection enhanced viral replication and infection pathogenesis in mice ( Sakuma et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we recently investigated the effects of macrophage depletion on SeVΔC pathogenesis and replication in mice. Depletion of airway macrophages via clodronate-loaded liposomes enhanced pathogenesis and viral replication in vivo ( Sakuma et al, 2021 ). Therefore, the suppression macrophage function may represent a major strategy evolved by these viruses to enhance their pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation